A 1, 2, 4-diazaphospholyl radical and its nitrogen–phosphorus coupled dimer: synthesis, X-ray structural characterization, EPR analysis, and computational studies1. Issue 63 (14th August 2015) - Su, Jing; Wang, Bingqiang; Liu, Dongling; Du, Libo; Liu, Yang; Su, Jihu; Zheng, Wenjun
<x xml:space="preserve">Abstract</x> The oxidation of 1, 2, 4-diazaphospholide potassium (K+[2−]) produced a neutral 1, 2, 4-diazaphospholyl radical (2˙) that was able to self-associate through a N–P coupling to give a 2(N)–2(P) dimer.